Becoming specific biological bicyclists 12–13 years under act of the specific loading - Пруднікова [Maryna Prudnikova], Марина Сергіївна; Мулик [Viacheslav Mulik], В’ячеслав Володимирович; Бізін [Viktor Bizin], Віктор Петрович (Slobozhanskyi Herald of Science and Sport, 2013)
Developed and implemented an experimental method of construction mesocycles normal phase ovarian-menstrual cycle during the formation of reproductive function of the female body. Studied and defined features of formation of the reproductive function of girls under the influence of specific loads for specially-preparatory and competitive phases of a year-long training macrocycle. The necessity of taking into account the emergence of a specific function in the biological cycle cyclists thoracic and muscular body types to reduce the exercise of his young body.